Synergistic activity of Malunggay (Moringa oleifera) leaves and Sodium percarbonate (2Na2CO3•3H2O2) as a wastewater deodorizer for pig farms - Stacy Eleoriene T. Arzadon (Northern Negros State College of Science and Technology (NONESCOST), 2022)
According to the Agriculture and Consumer Health Department (2017), odor is associated with the main environmental and societal problems throughout pig farms affecting 72% of nearby residents and 30% of workers in the Philippines (Drucker et al., 2007). The synergistic activity of Malunggay (Moringa oleifera) leaves with Sodium percarbonate (2Na2CO3•3H2O2) was aimed at deodorizing pig farm wastewaters to decrease the presence of odorant compounds. Investigations were: I. Screening for peroxidase, II. Laboratory analyses for Volatile Organic Compounds (VOCs), Hydrogen sulfide (H2S), and Ammonia (NH3), III. Perceptual Odor Assessment of Human Panel, IV. Shelf-life determination. Screening showed that malunggay leaves contain peroxidase, an enzyme that can convert toxic materials into less harmful substances (Albuquerque et al., 2019). For laboratory analyses in the experimental and negative control groups, the Colorimetry for H2S showed 48 mg/L and <1.0 mg/L respectively; Phenate method for NH3 showed 124 mg/L and 121 mg/L respectively; Gas Chromatography detected no other VOC except chloroform. 32 µg/L and 17 µg/L were found, respectively. Using the 9-point Hedonic scale for perceptual odor assessment of a human panel, results showed that in terms of odor intensity, there was an 82.76% decrease in the negative control (Strongest Odor Imaginable) to the experimental (Moderate Odor). While there was an 80% decrease in unpleasantness from the negative control (Extremely Unpleasant) to the experimental (Neutral Pleasantness). After shelf-life determination, the malunggay leaves powder lasted for 8 weeks. For further validation of results, additional studies on the synergistic activity of plant peroxidases and peroxides must be conducted with various methods of application and testing.